Of Mice and Men play still - Peter Stackpole:::Creator::::::::::::
In this Of Mice and Men play still from the Broadway theater production, George (Wallace Ford) tells Lennie (Broderick Crawford) 'Give me that mouse.' This performance took place on the Jungle Stage. RESTRICTED USE The original is in the safe (2 copies).